2023
DOI: 10.7554/elife.85847
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin administration enhances pleasantness and neural responses to gentle stroking but not moderate pressure social touch by increasing peripheral concentrations

Abstract: Background: Social touch constitutes a key component of human social relationships although in some conditions with social dysfunction, such as autism, it can be perceived as unpleasant. We have previously shown that intranasal administration of oxytocin facilitates the pleasantness of social touch and activation of brain reward and social processing regions, although it is unclear if it influences responses to gentle stroking touch mediated by cutaneous C-touch fibers or pressure touch mediated by other types… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…While there is still the possibility that some functional effects of the intranasal administration of oxytocin might be mediated via its direct entry into the brain via the olfactory and trigeminal nerves, which could not be achieved by an oromucosal route, evidence to date supports the conclusion that many functional effects are mediated by increased blood concentrations [ 4 , 16 , 33 , 34 , 35 , 40 , 50 ]. Most notably, in a recent study where the ability of intranasally administered oxytocin to enter the peripheral circulation was greatly reduced by the pre-administration of a vasoconstrictor (otrivine), the functional effects of a 24 IU intranasal oxytocin dose were almost completely eliminated.…”
Section: Discussion and Future Potential Developments And Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…While there is still the possibility that some functional effects of the intranasal administration of oxytocin might be mediated via its direct entry into the brain via the olfactory and trigeminal nerves, which could not be achieved by an oromucosal route, evidence to date supports the conclusion that many functional effects are mediated by increased blood concentrations [ 4 , 16 , 33 , 34 , 35 , 40 , 50 ]. Most notably, in a recent study where the ability of intranasally administered oxytocin to enter the peripheral circulation was greatly reduced by the pre-administration of a vasoconstrictor (otrivine), the functional effects of a 24 IU intranasal oxytocin dose were almost completely eliminated.…”
Section: Discussion and Future Potential Developments And Applicationsmentioning
confidence: 99%
“…The same protocol was therefore adopted as for intranasal administration with 6 × 4 IU doses being self-administered under and on top of the tongue and with each spray being given at 30 s intervals to match the intranasal protocol (i.e., a total administration duration of 3 min). To maximize absorption, subjects were required to keep the spray in their mouth without swallowing until they self-administered the next dose [ 33 , 34 , 35 ]. Initially, in these studies, a pharmacokinetic assessment was carried out in 10 male adult male subjects with blood samples being taken at 15 min intervals before and for 105 min after the lingual administration.…”
Section: Oromucosal Administration Of Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been found that the nose-to-blood route is more critical for the pharmacological effects of nasal OXT than the nose-to-brain route, and that nasal OXT produces its effects by increasing peripheral blood concentrations rather than directly entering the brain in the human subject [ 44 ]. In addition, Chen et al also confirmed that oral and nasal spray OXT increased peripheral circulating concentrations [ 45 ]. OXT selectively enhances C-touch fiber-targeted pleasurable responses to social touch processing via peripheral pathways rather than directly into the brain [ 45 ].…”
Section: Introductionmentioning
confidence: 95%